TO THE CONCEPT OF THE COURSE “COUNTRY STUDIES. RUSSIA FOR STUDENTS OF THE SPECIALTY "LANGUAGE AND LITERATURE (RUSSIAN)", STUDENTS IN UNIVERSITIES OF UKRAINE - Vetokhina, V.A.; Hamali О.I. (Pedagogy of Higher and Secondary Education, 2003)
No abstract.